Metabolomic Profiling of Respiratory Muscles and Lung in Response to Long-Term Controlled Mechanical Ventilation - Wen, Ya; Zhang, Xiang; Larsson, Lars (Frontiers in Cell and Developmental Biology, 2022)
Critical illness myopathy (CIM) and ventilator-induced diaphragm dysfunction (VIDD) are characterized by severe muscle wasting, muscle paresis, and extubation failure with subsequent increased medical costs and mortality/morbidity rates in intensive care unit (ICU) patients. These negative effects in response to modern critical care have received increasing attention, especially during the current COVID-19 pandemic. Based on experimental and clinical studies from our group, it has been hypothesized that the ventilator-induced lung injury (VILI) and the release of factors systemically play a significant role in the pathogenesis of CIM and VIDD. Our previous experimental/clinical studies have focused gene/protein expression and the effects on muscle structure and regulation of muscle contraction at the cell and motor protein levels. In the present study, we have extended our interest to alterations at the metabolomic level. An untargeted metabolomics approach was undertaken to study two respiratory muscles (diaphragm and intercostal muscle) and lung tissue in rats exposed to five days controlled mechanical ventilation (CMV). Metabolomic profiles in diaphragm, intercostal muscle and lung tissue were dramatically altered in response to CMV, most metabolites of which belongs to lipids and amino acids. Some metabolites may possess important biofunctions and play essential roles in the metabolic alterations, such as pyruvate, citrate, S-adenosylhomocysteine, alpha-ketoglutarate, glycerol, and cysteine. Metabolic pathway enrichment analysis identified pathway signatures of each tissue, such as decreased metabolites of dipeptides in diaphragm, increased metabolites of branch-chain amino acid metabolism and purine metabolism in intercostals, and increased metabolites of fatty acid metabolism in lung tissue. These metabolite alterations may be associated with an accelerated myofibrillar protein degradation in the two respiratory muscles, an active inflammatory response in all tissues, an attenuated energy production in two respiratory muscles, and enhanced energy production in lung. These results will lay the basis for future clinical studies in ICU patients and hopefully the discovery of biomarkers in early diagnosis and monitoring, as well as the identification of future therapeutic targets.